2013
DOI: 10.1021/es403527n
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation of Silver Nanoparticles: Natural Antidote to Their Toxicity

Abstract: Nanomaterials are highly dynamic in biological and environmental media. A critical need for advancing environmental health and safety research for nanomaterials is to identify commonly occurring physical and chemical transformations affecting nanomaterial properties and toxicity. Silver nanoparticles, one of the most ecotoxic and well-studied nanomaterials, readily sulfidize in the environment. Here, we show that very low degrees of sulfidation (0.019 S/Ag mass ratio) universally and significantly decreases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
307
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(327 citation statements)
references
References 67 publications
13
307
1
2
Order By: Relevance
“…For the WWTP effluent, however, the spiked recoveries were in the range of 106.2-149.9%, which can be attributed in part to the transformation of AgNPs to Ag 2 S NPs that commonly occur in WWTP. 10,[14][15][16] Overall, the results were good in view of the low spiking levels and matrix complexity, indicating that the proposed method is capable of the speciation analysis of Ag 2 S NPs in environmental samples. However, further studies are needed to obtain more satisfactory recoveries.…”
Section: Application In Real Water Sample Analysismentioning
confidence: 83%
“…For the WWTP effluent, however, the spiked recoveries were in the range of 106.2-149.9%, which can be attributed in part to the transformation of AgNPs to Ag 2 S NPs that commonly occur in WWTP. 10,[14][15][16] Overall, the results were good in view of the low spiking levels and matrix complexity, indicating that the proposed method is capable of the speciation analysis of Ag 2 S NPs in environmental samples. However, further studies are needed to obtain more satisfactory recoveries.…”
Section: Application In Real Water Sample Analysismentioning
confidence: 83%
“…However, the risks of particulate and nanosilver in the environment may be less than expected due to the favorable reaction of silver with sulphide (a common ion in sewage) to form precipitates and complexes which are stable even in oxidizing conditions (Choi et al, 2009;Kim et al, 2010;Kaegi et al, 2011) and importantly reducing the release of the toxic Ag ion (Levard et al, 2011). This form appears to reduce the toxicity of silver (Levard et al, 2013). It remains to be seen to what extent the diversion of silver to land through sewage sludge poses environmental risks.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity reduction has thus been associated to the formation of an insoluble precipitate that scavenges most of the Ag + ions from the solution and hence lowers their availability and action. Presence of sulfides is one of the most notable cases, due to the very low solubility of Ag 2 S. Several studies showed that presence of traces of this ion almost suppressed the biocidal activity of silver containing-systems, as seen in Fig. 2A [57][58][59]. Furthermore, both Reinsch et al [58] and Levard et al [59] showed an inhibition of the effect for S 2− /Ag molar ratio below 0.5 (which corresponds to the stoichiometric conditions).…”
Section: Role Of Ag + Speciesmentioning
confidence: 93%
“…Presence of sulfides is one of the most notable cases, due to the very low solubility of Ag 2 S. Several studies showed that presence of traces of this ion almost suppressed the biocidal activity of silver containing-systems, as seen in Fig. 2A [57][58][59]. Furthermore, both Reinsch et al [58] and Levard et al [59] showed an inhibition of the effect for S 2− /Ag molar ratio below 0.5 (which corresponds to the stoichiometric conditions). This was explained by the formation of an insoluble Ag 2 S layer around the Ag NPs, preventing further dissolution and hence activity.…”
Section: Role Of Ag + Speciesmentioning
confidence: 93%